The good news about worry : applying biblical truth to problems of anxiety and fear - Backus, William D. (Minneapolis, MN : Bethany House, 2010)
"A Christian psychologist explains how to ease and reduce anxiety by replacing worry-producing thoughts" --Provided by publisher.
Contents : Does everybody get anxious? -- The real culprit: avoidance -- The classic double bind -- The "disguises" of anxiety -- The spiritual roots of anxiety -- Two personalities -- Real causes of anxiety -- How free do you want to be? -- Washing in the river -- Laying yourself open -- Breaking the spiral -- Exploding your "myth beliefs" -- Moving the truth into your heart -- Accepting anxious feelings -- Lessening phobic anxiety -- Agoraphobia: fear of panic -- How to (almost) stop worrying.
Includes bibliographical references (p. [215]-219) and index.
Keywords: Anxiety (psychology) -- biblical teaching; Worry; Anxiety -- Religious aspects -- Christianity; Worry -- Religious aspects -- Christianity